Optimizing administrative efficiency in education departments: a knowledge management approach - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This study explores the implementation of knowledge management architecture in enhancing administrative efficiency and the quality of educational services within the Education Department. The primary issue addressed is this institution's administrative complexity, challenges in managing dispersed knowledge, and the need for more information technology integration. Research methods encompass qualitative and quantitative data analysis from interviews, observations, and surveys conducted with administrative staff. The findings indicate that applying knowledge management architecture significantly enhances administrative efficiency, reinforces collaboration among staff and teachers, and facilitates better decision-making. The contribution of this research lies in providing a robust foundation for policymakers and educational practitioners to implement measurable and sustainable knowledge management strategies to enhance the quality of educational services and strengthen the foundation for social and economic advancement.